2021
DOI: 10.1186/s40862-021-00119-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing auditory input for foreign language learners through a verbotonal-based dichotic listening approach

Abstract: The quality of the physical language signals to which learners are exposed and which result in neurobiological activity leading to perception constitutes a variable that is rarely, if ever, considered in the context of language learning. It deserves some attention. The current study identifies an optimal audio language input signal for Chinese EFL/ESL learners generated by modifying the physical features of language-bearing audio signals. This is achieved by applying the principles of verbotonalism in a dichot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Common methods used to explore gender differences in listening comprehension include dichotic listening, the Metacognitive Strategy Instruction (MetSI), and the Metacognitive Awareness Listening Questionnaire (MALQ) although some researches have used functional Magnetic Resonance Imaging (fMRI) as a measurement tool for this topic; however, the techniques of instructing this tool is rather complicated and costly which required funds and groups of researchers for longitudinal studies. In addition, as the study is complex and long-term experimental, participants in this type of research is rather limited (Cai et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common methods used to explore gender differences in listening comprehension include dichotic listening, the Metacognitive Strategy Instruction (MetSI), and the Metacognitive Awareness Listening Questionnaire (MALQ) although some researches have used functional Magnetic Resonance Imaging (fMRI) as a measurement tool for this topic; however, the techniques of instructing this tool is rather complicated and costly which required funds and groups of researchers for longitudinal studies. In addition, as the study is complex and long-term experimental, participants in this type of research is rather limited (Cai et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In cognitive studies, dichotic listening (e.g. Gruber & Gaebelein, 1979;Voyer, 2011;Cai et al, 2021), and recall/checklist recall were often used to evaluate gender differences in using brain hemispheres for listening comprehension. For instance, Gruber et al, (1979) implemented a study at the University of North Carolina at Greensboro for the first author's master's thesis experiment with the participation of 120 (60 males and 60 females) graduate and undergraduate college students.…”
Section: Methods Used To Explore Gender Differences In Listeningmentioning
confidence: 99%
“…In line with that, Guberina in 1972 and 1976 had worked on verbotonalism, or the verbotonal method, and demonstrated that integrating pronunciation, gesture, and movement (including dance) improves sound perception and pronunciation in contexts of foreign language learning (Lian, 2011). In the following years, researchers from China, Thailand, Indonesia, and Cambodia have experimented the verbotonal method and demonstrated its effectiveness on pronunciation (Lian, 1980) listening comprehension (Cai et al, 2021), speaking (Yang, 2016), reading (Alazard et al, 2012), and writing (Bumela, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we have had stunning examples of intellectual crowdsourcing such as the fold.it initiative, leading to what I call the growth of community intelligence. And remember that, most often, progress comes from the contributions of groups engaging in crazy actives such as the Focus on the Physical (FonPh) work (Cai et al, 2021;Lian et al, 2020) in neuroscience which focuses on the importance of the physical quality of the auditory input used in language-learning (but as Jack Ma said: we are crazy, but we are not stupid). Such craziness should be encouraged and initiatives such as this should help us to reduce the risk of stagnation and move the field forward.…”
Section: Social Networkingmentioning
confidence: 99%